(untitled) - Wilson, Diann (San Francisco, CA, 2005)
In The Other Blended Learning, Diann Wilson and Ellen Smilanich explain how to successfully blend a variety of learning methods?including mentoring, coaching, on-the-job training, and e-learning?around classroom-delivered content. Though blended learning is most often associated with e-learning, this ?other? blend shows how to maximize the classroom experience to aid learning transfer and improve performance.? Written in an easy-to-use format, The Other Blended Learning offers a practical guide for understanding and implementing a successful blended learning approach in any organization no matter what its size or mission.
Keywords: Employees,Internet in education,Computer-assisted instruction,Nhân viên,Internet trong giáo dục,Máy tính hỗ trợ giảng dạy; Training of.,Đào tạo